Analysis Of Changes In Customer Communication Patterns Through The Use Of The Myicon+ Application - Dea Firsta Airindita Putri; Dindin Dimyati (Green Publisher Indonesia, 2025)
The increasing digitalisation of business has prompted companies to enhance the efficacy of their systems, even in the absence of physical meetings, with the aim of meeting customer needs and enhancing satisfaction. This encompasses telecommunications service systems. The MyICON+ initiative was conceived as a pioneering endeavour aimed at enhancing accessibility to information, streamlining account management processes, and facilitating enhanced customer engagement with the organisation. The research focuses on the transition of service systems from conventional methods (telephone, WhatsApp, email) to the MyICON+ digital platform, and its impact on customer communication patterns. The present research employs a constructivist and phenomenological paradigm, underpinned by new media theory and a qualitative research method, through in-depth interviews complemented by passive observation. The findings indicate a substantial shift in customer preference, with a notable transition from conventional services to faster and more integrated applications, exhibiting an average response time of 2–6 minutes. The integration of features such as live chat, real-time fault tracking, and billing notifications has been demonstrated to enhance efficiency and customer satisfaction. Nevertheless, obstacles remain, including technical bugs during initial use, some customers' preference for call centres, and the need for further socialisation. Overall, MyICON+ has created a digital communication ecosystem that is dynamic, interactive, and user-friendly, while strengthening customer loyalty.